2013
DOI: 10.1210/jc.2012-3261
|View full text |Cite
|
Sign up to set email alerts
|

[123I]Iodometomidate Imaging in Adrenocortical Carcinoma

Abstract: Context

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(19 citation statements)
references
References 23 publications
0
19
0
Order By: Relevance
“…Imaging with metomidate labelled with 123 I (iodometomidate, [ 123 I]IMTO) can identify adrenocortical lesions with high specificity but is unable to differentiate benign from malignant lesions. In addition, retention of [ 123 I]IMTO in metastatic lesions can identify patients suitable for specific, targeted radioactive treatment. When available, [ 123 I]IMTO imaging might help to detect distant metastasis before surgery as well as recurrences, as it is an adrenocortical specific tracer.…”
Section: Preoperative Assessment Before Adrenalectomy For Suspected Accmentioning
confidence: 99%
“…Imaging with metomidate labelled with 123 I (iodometomidate, [ 123 I]IMTO) can identify adrenocortical lesions with high specificity but is unable to differentiate benign from malignant lesions. In addition, retention of [ 123 I]IMTO in metastatic lesions can identify patients suitable for specific, targeted radioactive treatment. When available, [ 123 I]IMTO imaging might help to detect distant metastasis before surgery as well as recurrences, as it is an adrenocortical specific tracer.…”
Section: Preoperative Assessment Before Adrenalectomy For Suspected Accmentioning
confidence: 99%
“…They did, however, highlight the validity of molecular imaging targeted to CYP11B1 and B2 to distinguish adrenocortical from non-adrenocortical tissue. Subsequent efforts focused on radiolabeling metomidate with isotopes of iodine, to provide more stable ligands with a longer half-life (permitting longer imaging times and clearance of the tracer to other sites away from the adrenals): 123 I-iodometomidate for SPECT imaging; 131 I-iodometomidate as a potential therapeutic radiopharmaceutical agent for treating ACC [48,49,50]; and possibly 124 I-iodometomidate as a PET tracer (although work with this remains pre-clinical) [48,49,50,51]. …”
Section: 123/124/131i-iodometomidate Imaging In Adrenal Diseasementioning
confidence: 99%
“…Hahner and colleagues have specifically evaluated 123 I-iodometomidate imaging in 58 patients with histologically-confirmed adrenocortical carcinoma, using the same methodology described previously [50,59]. 123 I-iodometomidate detected both primary and metastatic ACC.…”
Section: 123/131i-iodometomidate Imaging In Adrenocortical Carcinomentioning
confidence: 99%
“…123 I-metomidate was also evaluated in a prospective study of 58 patients with metastatic ACC, and was found to have 38% sensitivity and 100% specificity in detecting primary ACC and metastatic ACC lesions, numbers that were favorable compared with FDG-PET. A third of patients had 123 I-metomidate uptake in all lesions larger than 2 cm [41]. …”
Section: Evaluation and Work-upmentioning
confidence: 99%